An Indonesian Perspective of Father’s Involvement in Children’s Education: The Role of Religiosity, Marital Satisfaction, and Father’s Self-Efficacy - Fitriana, Dewi; Hanurawan, Fattah; Chusniyah, Tutut; Atmoko, Adi (Journal of Educational, Health and Community Psychology, 2025)
In Indonesia, traditional social norms continue to emphasize the father as the dominant and authoritative figure in family life. However, research on fathers' involvement in children's education and the factors influencing it remains limited. This study investigates the alignment between a theoretical model of father involvement and empirical data, specifically examining the impact of religiosity, marital satisfaction, and fathers' self-efficacy on their participation in children's education. The study surveyed 393 fathers of state junior high school students in Malang, Indonesia, using four standardized instruments: the Father’s Involvement Scale, Religiosity Scale, Marital Satisfaction Scale, and Father’s Self-Efficacy Scale. Structural equation modeling (SEM) analysis confirmed a strong fit between the theoretical framework and empirical findings. Results indicate that religiosity has a direct influence on father involvement and marital satisfaction but does not significantly affect involvement indirectly through marital satisfaction. Marital satisfaction, in turn, has a significant impact on both father involvement and self-efficacy, while self-efficacy directly contributes to greater involvement in children's education. Based on these findings, schools are encouraged to actively engage fathers in educational activities to enhance their role in adolescent education. Given the study's quantitative approach, future research should consider a mixed-methods design to provide a more comprehensive understanding of father involvement in adolescent education.